2005
DOI: 10.2337/diabetes.54.11.3274
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Diabetic Nephropathy Is Related to Dicarbonyl and Oxidative Stress

Abstract: Dicarbonyl and oxidative stress may play important roles in the development of diabetes complications, and their response to hyperglycemia could determine individual susceptibility to diabetic nephropathy. This study examines the relationship of methylglyoxal, 3-deoxyglucosone (3DG), and oxidative stress levels to diabetic nephropathy risk in three populations with diabetes. All subjects in the Overt Nephropathy Progressor/Nonprogressor (ONPN) cohort (n ‫؍‬ 14), the Natural History of Diabetic Nephropathy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 57 publications
7
128
1
2
Order By: Relevance
“…Our observations that Glo1 overexpression reduced diabetes-induced vascular and renal dysfunction, as well as data from other studies [30,42,43], support a role for glycation in these pathogeneses. In addition, a cohort study by Beisswenger et al showed that progression of diabetic nephropathy is also significantly related to elevation in dicarbonyl stress [11]. In this study elevated levels of MGO correlated with loss of podocytes, another mechanism preceding glomerular leakage [44].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our observations that Glo1 overexpression reduced diabetes-induced vascular and renal dysfunction, as well as data from other studies [30,42,43], support a role for glycation in these pathogeneses. In addition, a cohort study by Beisswenger et al showed that progression of diabetic nephropathy is also significantly related to elevation in dicarbonyl stress [11]. In this study elevated levels of MGO correlated with loss of podocytes, another mechanism preceding glomerular leakage [44].…”
Section: Discussionmentioning
confidence: 53%
“…MGO is known to have detrimental effects on cellular function and it is also evident that elevated levels of MGO are responsible for renal oxidative stress, as demonstrated in diabetic rats [10]. Most importantly, progression of hypertension and diabetic nephropathy in humans is also significantly related to increased levels of MGO [11,12].…”
Section: Introductionmentioning
confidence: 95%
“…An important issue raised by our experiments deals with the contribution of Rac-1-mediated ROS production in EGFR activation as well as in the signaling cascade promoting MC cell cycle progression upon ox-LDL. Susceptibility to diabetic nephropathy mainly relies on oxidative stress (44), and increased levels of ROS in association with up-regulation of the gp91 phox and Rac-1 expression have been reported in diabetes (45). Thus, our data add further insight into the molecular mechanisms promoting early MC hypertrophy in diabetes-associated renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…MG-H1 residues are a major type of protein damage by glycation in diabetes, occurring on both cellular and extracellular proteins (20,21). Increased concentration of MG-H1 residues in plasma protein of diabetic patients was not linked directly to A1C (22), probably because methylglyoxal formation is increased in both fasting and postprandial hyperglycemia (16,23) and influenced by factors other than hyperglycemia (low glyceraldehyde-3-phosphate dehydrogenase activity [24]). MG-H1 residue formation occurred at susceptible hotspot sites in proteins with loss of functional activity (19).…”
mentioning
confidence: 99%